The development of historical writing in the European Renaissance (15-19 AD) (political and cultural factors)) (Revue El-Wahat pour les Recherches et les Etudes, 2025)
Europe during the Renaissance witnessed a remarkable development in historical writing among Europeans, especially as it was simple before this era in its level, neither in terms of the systematic collection of sources, nor in terms of the absence of a deep research work in the study. . . .Reading the historical event in the Middle Ages was characterized by a clear religious influence that made it misleading, as it is based on reading, writing and interpreting history only through the ecclesiastical concept.    This development would not have occurred without a set of foundations and factors that drove it to this stage of development, whether it was political related to the beginning of European political stability and the subsequent movement of geographical discoveries, or cultural factors related to cultural communication. Among the Europeans. And Muslims through important stations, most notably Andalusia. Through it, the Islamic sciences were translated into European languages, including historical writings. In addition to all this, European thought was freed from the control of the Church and the Orientalist movement appeared.All these variables formed the basis of the dawn of a new era in Europe, where historical writing paved its way.towards distinction and liberation, and thus laid the foundation for building a renewed historical thought.Keywords: Historical writing ; Europe , Renaissance , political , translation,cultural.